2019
DOI: 10.1002/ente.201900925
|View full text |Cite
|
Sign up to set email alerts
|

Chemical‐Looping Conversion of Methane: A Review

Abstract: Chemical‐looping technology provides a versatile platform to convert methane in a clean and efficient manner, achieving CO2 capture and generation of syngas/pure H2 without additional separation processes (e.g., separation of CO2 from N2‐diluted exhaust gases, separation of O2 from air, and separation of H2 from syngas) using a two‐step redox concept through recyclable oxygen storage materials (named oxygen carriers) as intermediates. The design and elaboration of appropriate oxygen carriers is a key issue to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 274 publications
0
86
0
Order By: Relevance
“…We also note the recently published reviews on oxygen carrier formulation for various chemical looping applications. [24][25][26][27] These reviews have comprehensively captured the recent advances in the development of oxygen carriers for the conversion of gaseous and liquid hydrocarbon fuels to heat and, or functional chemical products. However, we identify an outstanding need to complement the existing literature and to establish a comprehensive understanding of the structural-functional relationship of OCs used in CLBP.…”
Section: Aims and Objectivesmentioning
confidence: 99%
“…We also note the recently published reviews on oxygen carrier formulation for various chemical looping applications. [24][25][26][27] These reviews have comprehensively captured the recent advances in the development of oxygen carriers for the conversion of gaseous and liquid hydrocarbon fuels to heat and, or functional chemical products. However, we identify an outstanding need to complement the existing literature and to establish a comprehensive understanding of the structural-functional relationship of OCs used in CLBP.…”
Section: Aims and Objectivesmentioning
confidence: 99%
“…In contrast, the partial substitution of iron oxide with ceria did not improve the performance significantly [26]. Other oxygen carrier compositions have been reviewed recently [29,30], and from these studies, it is apparent that mixed oxides composed of several redox-active oxides can have synergistic effects with regard to their activity and syngas selectivity. An important problem to overcome in the chemical looping-based reforming scheme is the deposition of carbon on the surface of the oxygen carrier due to the cracking reaction of methane that is catalyzed by metallic iron.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon deposits could potentially be combusted in the oxidation step of the process (see below) and therefore lower the CO 2 capture efficiency. Perovskite-based oxygen carriers (e.g., LaFeO 3 with various dopants partially substituting the cations La and Fe) have shown promise in reducing carbon deposition while possessing a high selectivity towards syngas and a high reactivity due to their high oxygen mobility [30]. Our recent experimental studies have demonstrated that some perovskite-based oxygen carrier formulations (e.g., La 0.85 Sr 0.15 FeO 3 or La 0.85 Sr 0.15 Fe 0.95 Al 0.05 O 3 ) possess excellent long-term stabilities in reactor systems of different scales.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the ability to transport lattice oxygen atoms and heat, oxygen carriers (OCs) play a vital role in the processes of chemical looping 1‐3 . In the past 10 years, nearly 1200 kinds of oxygen carriers have been developed and evaluated 4 .…”
Section: Introductionmentioning
confidence: 99%